Los salarios minimos y su incidencia en el nivel de empleo en el Ecuador periodo 2007-2015 - Cepeda Balla, José Luis (2017)
The following study has as main objective to analyze "THE MINIMAL WAGES AND ITS INCIDENCE IN THE LEVEL OF EMPLOYMENT IN ECUADOR. PERIOD 2007-2015 ", which allows us to find the main characteristics of the two study variables, as well as to quantify the influence of minimum wages on job training. Chapter I, Reference Frame, introduces the introduction, problem statement, general and specific objectives, as well as the justification of the research. For Chapter II, the theoretical framework of the research allows to know the theoretical basis of the two variables. Particularly we study definitions, classifications, legal framework types of employment. In the second part, an analysis of the labor market, the formation of employment and the different currents that explain it. This chapter concludes with a review of the legal framework in the country. Chapter III, Methodological Framework, explains the methods and methodologies used in the present investigation. It explains the method used, as well as an analysis of the types and designs of the research. In the analysis of the results, a validation and analysis of the elements of the main variables of the labor market of the country, as well as of the main indicators of employment are elaborated. An analysis of the evolution of the minimum wage and its components is also made. Finally an econometric model is elaborated, that allows to find the incidence of the minimum wage and the level of employment. Chapter IV presents the conclusions and recommendations obtained with the research.